Spatial patterns of multiple malnutrition types in West Africa: Four country case studies - Diop, Loty; van den Bold, Mara; Guo, Zhe; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
Low- and middle-income countries (LMICs), including in Africa south of the Sahara, face a “new nutrition reality” (Popkin, Corvalan, and Grummer-Strawn 2020) referred to as the double burden of malnutrition, where children under five years of age (U5s) and women of reproductive age (WRA) continue to experience high rates of undernutrition while, at the same time, the rates of overweight and obesity in these populations are on the rise (Development initiatives 2020).